Construction of carnations-like Mn3O4@NiCo2O4@NiO hierarchical nanostructures for high-performance supercapacitors. (10th June 2019) - Feng, Xuansheng; Huang, Ying; Li, Chao; Xiao, Yuyang; Chen, Xuefang; Gao, Xiaogang; Chen, Chen
Abstract: Reasonable design for structure and composition of multi-component metal oxides is an effective and promising way to improve electrochemical performance of electrode materials. In this work, novel carnations-like Mn3 O4 @NiCo2 O4 @NiO hierarchical nanostructures are constructed by introducing CATB as structure-directing agents and adjusting hydrothermal reaction time. The perfect architecture maximizes the synergistic effect between components, providing more electrochemical reactive sites and promoting the diffusion and transfer of electrolyte ions. As a result, Mn3 O4 @NiCo2 O4 @NiO electrodes deliver an enhanced specific capacitance of 1905 F g −1 at 1 A g −1 and outstanding cyclic stability (92% of its initial capacitance is retained after 10000 cycles). Furthermore, ASC device which is assembled by the Mn3 O4 @NiCo2 O4 @NiO and activated carbon achieve excellent energy densities of 76.8 W h kg −1 at power densities of 800 W kg −1, proving the optimized Mn3 O4 @NiCo2 O4 @NiO is promising electrode material for supercapacitor. In addition, this work supplies helpful insights into rational design for structure and composition of multi-component metal oxides for enhancing electrochemical performance.